Synthesis method of polyimide resin

By using a dual asymmetric centrifuge bladeless mixer and high-speed mixing technology in the synthesis of polyimide resin, rapid synthesis with high solid content and low viscosity is achieved, solving the problems of long reaction time and difficult processing in traditional methods, and excellent mechanical properties and thermal stability are obtained.

CN119708481AActive Publication Date: 2025-03-28HUNAN SONGJING ADVANCED SURFACE TREATMENT & FUNCTIONAL COATING RES INST CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411912036.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing polyimide resin has high viscosity and poor fluidity under high solid content, which makes processing difficult. The traditional synthesis method has a long reaction time, insufficient reaction, and easy to agglomerate gels.

Method used

The reaction material was added in two steps with a double asymmetric centrifuge bladeless mixer. Combined with high-speed mixing technology, the reaction time is shortened and the molecular chain growth is controlled. Through the control of monomer ratio and reaction time, combined with monofunctional anhydride end capping, the low viscosity and high solids content of polyimide resin are achieved.

Benefits of technology

The rapid synthesis of high solid content and low viscosity polyimide resin is achieved, which shortens the reaction time and improves production efficiency. The obtained polyimide film has excellent mechanical properties and thermal stability, reducing processing difficulty and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205941470000091
    Figure BDA0005205941470000091
  • Figure BDA0005205941470000111
    Figure BDA0005205941470000111
  • Figure BDA0005205941470000131
    Figure BDA0005205941470000131
Patent Text Reader

Abstract

The invention belongs to the technical field of imide resin synthesis, and relates to a polyimide resin synthesis method, which comprises: mixing a diamine monomer, a dianhydride monomer and a solvent, placing in a bladeless mixer of a double asymmetric centrifuge, and dispersing for 10-40 min at a rotating speed of 1000-2500rpm; then adding an anhydride compound, and dispersing for 5-20 minutes at the rotating speed of 1000-2500rpm, so as to obtain polyimide resin; the total weight of the dianhydride monomer and the diamine monomer accounts for 25wt%-35wt% of the total reaction system. Under the condition that other special reagents are not added, by utilizing a special synthesis device, the processing performance of the polyimide resin is ensured, and meanwhile, the adverse effects on the mechanical property and the thermal stability are effectively avoided. And the synthesis method has the advantages of short reaction time, high synthesis efficiency and strong applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of imide resin synthesis and relates to a method for synthesizing a polyimide resin. Background Art

[0002] Polyimide is a kind of high-performance polymer containing imide rings in the main chain of the molecule. It is widely used in aviation, aerospace, microelectronics, rail transportation and nuclear industry due to its excellent thermomechanical properties, radiation resistance, low thermal expansion coefficient and electrical insulation. There are many different synthesis processes for polyimide, mainly including melt polycondensation, solution polycondensation, interfacial polycondensation and vapor deposition. The current mainstream and widely used synthesis route is solution polycondensation: that is, in a non-protonic polar solvent, through a condensation polymerization reaction under low temperature conditions, the diamine and dianhydride monomers are converted into a polyamic acid solution after 6-8 hours of reaction. However, when the solid content is high, the strong interaction between the polymer molecular chains can easily lead to a sharp increase in the viscosity of the solution. In extreme cases, it can also cause the solution to gel and lose processability.

[0003] Generally, polyimide resins have high viscosity and poor coating performance, and often need to be diluted with solvents to reduce viscosity before use. For example, in the prior art (Huang Chaobo, Zhang Hean, Peng Xinwen, et al. Synthesis and Performance Characterization of High-Strength Polyimide [J]. Polymer Materials Science and Engineering, 2007, 23 (4)), a polyimide precursor polyamic acid solution with ultra-high molecular weight is first synthesized, and a solvent is needed to dilute the solid content to 5% for good coating. This makes the processing process more complicated and cumbersome, significantly increases the cost, and exacerbates the problem of environmental pollution.

[0004] When the solid content is further increased, the viscosity of the polyimide resin will further increase, and the processability and operability will deteriorate sharply. In order to overcome this problem, the prior art CN110229333B uses thioglycolic acid and its derivatives to lock dialdehyde or polyaldehyde compounds and diamine-terminated polyamic acid main chain (imide) to form high molecular weight or cross-linked polyamic acid, and obtains a polyimide with a new structure after imidization. Although this method can obtain a new type of low-viscosity polyimide resin through a specific structure, enriches the structure of existing polyimide, and expands the application field of polyimide, it does not fundamentally solve the problem of high viscosity of existing general-purpose polyimide resins.

[0005] The prior art CN112029099B adopts a staged heating and feeding method to obtain a low-viscosity, high-solid content polyamic acid solution. The polyimide film made therefrom has excellent thermal stability, good mechanical properties and low thermal expansion coefficient, but the high solid content is only 19%. As the viscosity of the polyimide solution increases with the increase of the solid content, if the solid content is increased to more than 20% or even 30%, this method may no longer be applicable or may not achieve the expected effect.

[0006] The prior art CN101117384B prepares an amic acid ester oligomer, but due to the low molecular weight of the polyamic acid precursor, it has good controllability, can achieve a smooth coating effect, and can still maintain a low viscosity at a high solid content; and in the curing stage, the oligomer can be further polymerized into larger molecules to improve the mechanical properties of the final polyimide film. Unfortunately, even if the oligomer increases the molecular chain length by chain extension during the curing stage, the tensile strength of the final polyimide is only 78.896MPa, and the elongation at break is only 11.185%. The mechanical properties are still very different from those of conventional polyimides, and cannot meet the vast majority of polyimide application scenarios.

[0007] In addition, viscosity reduction can also be achieved by adding special additives to the polyamic acid resin. For example, in the prior art CN103788651B, trimethylchlorosilane is added to the polyamic acid solution. However, due to the presence of halogens and the corrosiveness of trimethylchlorosilane to certain metals and alloys, it may cause defects such as equipment damage and failure, which limits its application. Moreover, when the amount of trimethylchlorosilane added is large enough, as described in the patent, the addition amount of 40% can have a sufficiently good effect, but at this time, it has a significant impact on the solid content of the original polyamic acid solution, that is, the solid content is greatly reduced after the addition of trimethylchlorosilane. Prior art CN114181392A realizes partial chemical imidization by adding a certain amount of acetic anhydride and pyridine. The mechanism of acetic anhydride and pyridine to partially chemically imidize polyamic acid is that it can be used as a dehydrating agent to promote imide ring closure, but imidization ring closure will dehydrate, that is, there will be a certain amount of moisture in the system after partial imidization, and polyamic acid is unstable to water, and it is very easy to hydrolyze and break the chain, so after adding acetic anhydride and pyridine, the storage stability of polyamic acid solution will be seriously affected. Prior art CN112409612A is by adding carboxylic acid ammonium salt Gemini surfactant, but the whole reaction is more complicated and the reaction time is longer, and the total reaction time is close to 30h. Prior art CN111808285A adopts a mixed solution of triethylamine and water, a mixed solution of dimethylethanolamine and water, or a mixed solution of dimethylethanolamine and methanol as an active auxiliary agent, but the method needs to heat up and heat during reaction and continue to stir at high temperature for about 6h. The prior art CN104292459B adds a certain proportion of adhesion promoter on the basis of adding the end-capping agent, but the toughness of the polyimide film is poor, and the elongation at break is only between 10-15%. Although the above methods can obtain low-viscosity polyamic acid resin and improve its subsequent processability, there are various problems, mainly including complex synthesis or preparation process, poor controllability, poor product performance or storage stability, affecting the solid content of the product and the risk of damaging the substrate. Summary of the invention

[0008] The object of the present invention is to provide a method for synthesizing a polyimide resin having low viscosity at a high solid content.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] A method for synthesizing a polyimide resin comprises the following steps:

[0011] The diamine monomer, the dianhydride monomer and the solvent are mixed and placed in a dual asymmetric centrifuge bladeless mixer, and dispersed at a rotation speed of 1000-2500rpm for 10-40min; then an anhydride compound is added and dispersed at a rotation speed of 1000-2500rpm for 5-20min to obtain a polyimide resin; the total weight of the dianhydride monomer and the diamine monomer accounts for 25wt%-35wt% of the total reaction system.

[0012] The purpose of the present invention is to overcome the problems of high viscosity, poor fluidity and great processing difficulty of high solid content polyimide resin and the problem of long synthesis reaction time of polyimide resin, and to provide a rapid synthesis method of high solid content and low viscosity polyimide resin. In addition, the polyimide film prepared by the polyimide resin synthesized by the method has excellent mechanical properties and thermal stability.

[0013] The invention adopts a special dual asymmetric centrifuge bladeless mixer as a reaction device, and adds reaction materials in two steps, thereby simplifying the feeding and reaction steps of polyimide synthesis; and utilizes a high-speed mixing method to increase the reaction rate, thereby greatly shortening the condensation reaction time of the polyimide resin; in addition, the heat generated by the high-speed mixing and the reaction exothermic heat limits the forward reaction degree of the condensation reaction, which can effectively limit the disordered growth of the molecular chain, and realizes the molecular weight control of the polyimide resin by controlling the monomer ratio and the reaction time and combining the monofunctional acid anhydride for end-capping, thereby obtaining a high-solid and low-viscosity polyimide resin.

[0014] In one preferred embodiment, the dual asymmetric centrifuge bladeless mixer is a SpeedMixer high-speed mixer.

[0015] High-speed mixers achieve uniform mixing of reaction materials through high-speed shearing and impact, which is the basis for rapid reaction. Compared with traditional stirring methods, high-speed mixers can significantly increase the contact area and collision frequency between materials, thereby promoting the reaction.

[0016] In one preferred embodiment, the viscosity of the polyimide resin is 3000-20000 mPa·s.

[0017] In a preferred embodiment, the diamine monomer is one or more of 4,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, benzyl diamine, diaminodiphenylmethane, ethylenediamine, propylenediamine, perfluorodiamine, and helical bisfluorenediamine.

[0018] In one preferred embodiment, the dianhydride monomer is one or more of pyromellitic dianhydride, 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, monoether tetracarboxylic dianhydride, hexafluoro dianhydride, benzophenone tetracarboxylic dianhydride, tetramethylbiphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, pyridine dianhydride, cyclobutane tetracarboxylic dianhydride, butane tetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride, fluorine-containing dianhydride, and silicon-containing dianhydride.

[0019] In a preferred embodiment, the acid anhydride compound may be one or more of maleic anhydride, norbornene dicarboxylic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride.

[0020] In a preferred embodiment, the solvent is a highly polar aprotic solvent.

[0021] In one preferred embodiment, the solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, hexamethylphosphoric triamide, acetone, pyridine, and quinoline.

[0022] In a preferred embodiment, the solvent is a mixture of dimethylacetamide and N-methylpyrrolidone.

[0023] In one preferred embodiment, in the mixture, the mass ratio of dimethylacetamide to N-methylpyrrolidone is 80-90:8-15.

[0024] In one preferred embodiment, the molar ratio of the diamine monomer to the dianhydride monomer is 1.0:(0.95-0.995).

[0025] In one preferred embodiment, the molar ratio of the anhydride compound to the diamine monomer is 0.01-0.1:1.0.

[0026] The present invention will be further explained below:

[0027] The present invention successfully reduces the viscosity of high-solid-content polyimide resin by utilizing a special synthesis device without adding other special reagents; and by controlling the monomer ratio and reaction time, a low-viscosity polyimide resin with a precise viscosity range can also be obtained. While ensuring the processing performance of the polyimide resin, the adverse effects of the prior art on the mechanical properties and thermal stability of the finally obtained polyimide product are effectively avoided. In addition, the synthesis method requires a short reaction time and has high synthesis efficiency. In particular, in view of the problems of insufficient reaction, long reaction time, and easy agglomeration of gel caused by poor mass transfer of high-solid-content polyimide resin through mechanical stirring, the present invention has stronger applicability, that is, the method can be used to obtain a polyimide resin of excellent quality very simply and quickly.

[0028] The two-step method adds the main reaction materials, simplifies the feeding steps, and reduces the operational complexity and errors caused by multiple feedings. The two-step feeding combined with high-speed mixing ensures that all reactants are evenly mixed in a short time, thereby improving the reaction efficiency. The traditional method requires multiple feedings, and each feeding requires stirring and waiting for the reaction to proceed. The present invention adopts a two-step method to add the reaction materials, simplifies the feeding steps, and reduces the operational complexity and errors. This simplification not only saves time, but also improves the accuracy and consistency of the synthesis.

[0029] The mechanical energy and thermal energy generated by high-speed mixing promote the collision and combination of reactant molecules. Compared with static reactions, high-speed mixing significantly shortens the condensation reaction time and improves production efficiency.

[0030] The exothermic reaction limits the degree of the forward reaction of the condensation reaction: the heat generated during the reaction increases the temperature of the reaction system, thereby affecting the equilibrium state of the reaction. By controlling the stirring speed and stirring time, the disordered growth of the molecular chain can be effectively limited, avoiding excessive viscosity and gelation of the resin.

[0031] Monomer ratio and reaction time control combined with monofunctional anhydride end-capping: The monomer ratio determines the molecular structure of the polyimide resin, the reaction time affects the degree of reaction, and the monofunctional anhydride end-capping is used to control the molecular weight. These three factors work together to achieve precise control of the molecular weight of the polyimide resin, ensuring the low viscosity and excellent processing performance of the resin.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. Rapid synthesis: The dual asymmetric centrifuge bladeless mixer and one-time feeding significantly shorten the synthesis time of polyimide resin and improve production efficiency. According to preliminary experimental data, the synthesis method of the present invention can shorten the reaction time to 1 / 10 to 1 / 8 of the traditional method, and the specific shortening ratio depends on the reaction scale and conditions.

[0034] 2. High solid content and low viscosity: By controlling the reaction conditions and monomer ratio, the low viscosity synthesis of high solid content polyimide resin is achieved, solving the problem of high viscosity and poor fluidity of high solid content resin in the prior art. Experimental data show that when the solid content reaches 30% to 35%, the viscosity of the resin can still be maintained at a low level (such as within the range of 500-20000cp), which is much lower than the viscosity of the same solid content resin synthesized by traditional methods.

[0035] 3. Excellent processing performance: Low-viscosity polyimide resin has better fluidity, is easy to process and mold, and reduces the difficulty of processing. Experimental data show that compared with traditional high-viscosity resins, the low-viscosity resin synthesized by the present invention can reduce the number of coatings and mold filling time under the same processing conditions. Due to the enhanced fluidity of the resin and uniform viscosity, defects such as bubbles and cracks are not easy to occur during the processing. This helps to improve the quality and reliability of the final product.

[0036] 4. Excellent quality: The film prepared by the polyimide resin synthesized by this method has excellent mechanical properties and thermal stability. After mechanical property tests, its tensile strength and elongation at break are not inferior to those of resin films synthesized by traditional methods. At the same time, thermal stability tests show that the film can still maintain stable performance at high temperatures and is not easy to decompose or deform, meeting the application requirements of high-performance materials.

[0037] 5. Wide applicability: This method is particularly suitable for the synthesis of high-solid content polyimide resins, solving the problems of insufficient reaction, long reaction time and easy agglomeration of gel caused by poor mass transfer in traditional mechanical stirring.

[0038] 6. Low cost: The present invention reduces production costs by improving synthesis efficiency and simplifying operation steps. At the same time, due to the excellent performance of the resin and good processing performance, the scrap rate and rework rate can be reduced, further reducing production costs.

[0039] 7. Environmental protection: The present invention adopts environmentally friendly raw materials and process conditions in the synthesis process, reducing the emission and waste of harmful substances. At the same time, the low-viscosity resin is easier to recycle and reuse during the processing process, which helps to save resources and protect the environment.

[0040] In summary, the present invention provides an efficient and simple method for synthesizing a high-solid content and low-viscosity polyimide resin, which has significant technical advantages and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 FTIR spectra of polyimide films prepared in Examples and Comparative Examples. DETAILED DESCRIPTION

[0042] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention by adopting other various specific embodiments according to the content disclosed in the present invention, or any simple changes or modifications made by adopting the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict. The reaction temperature is room temperature.

[0043] Example 1

[0044] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 20.721 g (0.095 mol) of pyromellitic anhydride (PMDA), 88 g of dimethylacetamide (DMAc) and 10 g of N-methylpyrrolidone (NMP) solvent were added into a container, the container was sealed and placed into a SpeedMixer high-speed mixer, the speed was set to 1500 rpm, and after the reaction was continued for 30 min, 0.981 g (0.01 mol) of maleic anhydride (MA) was added and continued to mix at high speed for 10 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 3610 mPa·s.

[0045] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0046] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 1.

[0047] Example 2

[0048] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.049 g (0.0965 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 1500 rpm, and after the reaction was continued for 30 min, 0.686 g (0.007 mol) of maleic anhydride (MA) was added and continued to mix at high speed for 10 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 5160 mPa·s.

[0049] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0050] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 1.

[0051] Example 3

[0052] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.267 g (0.0975 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 1500 rpm, and after the reaction was continued for 30 min, 0.490 g (0.005 mol) of maleic anhydride (MA) was added and continued to mix at high speed for 10 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 7610 mPa·s.

[0053] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0054] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 1.

[0055] Example 4

[0056] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 1500 rpm, and after the reaction was continued for 30 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 1500 rpm for 10 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 12650 mPa·s.

[0057] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0058] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 1.

[0059] Example 5

[0060] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.703 g (0.0995 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 1500 rpm, and after the reaction was continued for 30 min, 0.098 g (0.001 mol) of maleic anhydride (MA) was added and continued to mix at 1500 rpm for 10 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 19800 mPa·s.

[0061] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0062] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 1.

[0063] Comparative Example 1

[0064] (1) 20.024 g (0.1 mol) of 4,4'-diaminodiphenyl ether (ODA), 21.812 g (0.1 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 1500 rpm, and after the reaction was continued for 30 min, 0.098 g (0.001 mol) of maleic anhydride (MA) was added and continued to mix at 1500 rpm for 10 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 47200 mPa·s.

[0065] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0066] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 1.

[0067] Comparative Example 2

[0068] (1) Using a conventional polyamic acid synthesis method, 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA) was added to a three-necked flask, 88 g of DMAc was added, and the mixture was stirred with a cantilever stirrer until the ODA was completely dissolved. Then, 20.721 g (0.095 mol) of pyromellitic dianhydride (PMDA) was added three times within 1 h, 10 g of NMP was added, and stirring was continued for 6 h. Finally, 0.981 g (0.01 mol) of maleic anhydride (MA) was added and the reaction was continued for 2 h to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 148800 mPa·s.

[0069] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0070] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 1.

[0071] Comparative Example 3

[0072] Using a conventional polyamic acid synthesis method, 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA) was added to a three-necked flask, and 88 g of DMAc was added and stirred until ODA was completely dissolved. Then, 21.812 g (0.1 mol) of pyromellitic dianhydride (PMDA) was added three times within 1 hour, and 10 g of NMP was added and stirred continuously. As the reaction proceeded, the viscosity of the reaction liquid increased rapidly and then gelled. The reaction was terminated and no homogeneous polyamic acid solution could be obtained.

[0073] Through the viscosity and mechanical property test results of Examples 1 to 5 and Comparative Examples 1 to 3, it can be found that with the increase of the molar ratio of dianhydride and the decrease of the molar ratio of maleic anhydride, the viscosity of the synthesized polyamic acid tends to increase, and the tensile strength and elongation at break also gradually increase. This means that the viscosity and performance of the synthesized polyamic acid can be effectively controlled by adjusting the monomer ratio; compared with the conventional polyamic acid synthesis method, it can be found that although the viscosity of the polyamic acid obtained by the dual asymmetric centrifuge bladeless mixer is lower, the performance is not greatly reduced. In terms of comprehensive viscosity and mechanical properties, Example 4 is better.

[0074] Table 1 Viscosity of polyamic acid and mechanical properties of its films at different monomer ratios

[0075]

[0076] Example 6

[0077] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 1000 rpm, and after the reaction was continued for 30 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 1000 rpm for 15 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 18800 mPa·s.

[0078] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0079] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 2.

[0080] Example 7

[0081] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 30 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 15 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 10160 mPa·s.

[0082] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0083] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 2.

[0084] Example 8

[0085] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2500 rpm, and after the reaction was continued for 30 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 2500 rpm for 15 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 7880 mPa·s.

[0086] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0087] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 2.

[0088] Comparative Example 4

[0089] (1) Using a conventional polyamic acid synthesis method, 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA) was added to a three-necked flask, 88 g of DMAc was added, and the mixture was stirred with a cantilever stirrer until ODA was completely dissolved. Then, 21.485 g (0.0985 mol) of pyromellitic dianhydride (PMDA) was added three times within 1 h. After 10 g of NMP was added, stirring was continued at a speed of 80 rpm for 6 h. Finally, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and the reaction was continued for 2 h to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 672500 mPa·s.

[0090] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0091] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 2.

[0092] Comparative Example 5

[0093] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 500 rpm, and after the reaction was continued for 30 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 500 rpm for 15 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 22100 mPa·s.

[0094] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0095] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 2.

[0096] Table 2 shows the viscosity and mechanical properties of Example 4, Examples 6-8 and Comparative Examples 4-5. The fixed monomer ratio and different rotation speeds also have a great influence on the viscosity of polyimide, that is, the faster the rotation speed, the lower the viscosity, and the mechanical properties increase first and then decrease with the increase of the rotation speed. Among them, Example 7 has the best comprehensive performance, and its mechanical properties are close to those of the film prepared by the conventional synthetic polyamic acid. Comparative Example 4 adopts the traditional polyamic acid synthesis method, and the viscosity is extremely large, reaching more than 650,000, and it is impossible to achieve high solid and low viscosity; the comparative example uses a high-speed mixer with a relatively low rotation speed, but its viscosity is relatively high and the mechanical properties are not good.

[0097] Table 2 Viscosity of polyamic acid and mechanical properties of its films at different rotation speeds

[0098]

[0099] Example 9

[0100] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 10 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 5 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 17660 mPa·s.

[0101] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0102] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 3.

[0103] Example 10

[0104] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 20 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 10 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 15320 mPa·s.

[0105] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0106] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 3.

[0107] Embodiment 11

[0108] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 40 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 20 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 6370 mPa·s.

[0109] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0110] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 3.

[0111] Comparative Example 6

[0112] 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 5 minutes, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 2.5 minutes. The reaction was not complete, and some monomers were still involved, and a homogeneous and transparent polyamic acid solution could not be obtained.

[0113] Comparative Example 7

[0114] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 21.485 g (0.0985 mol) of pyromellitic anhydride (PMDA), 88 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 60 min, 0.294 g (0.003 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 30 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 2530 mPa·s.

[0115] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0116] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 3.

[0117] Table 2 shows the viscosity and mechanical property data of Example 7, Examples 9 to 11 and Comparative Examples 6 to 7. When only the reaction time is changed, the viscosity of the polyamic acid gradually decreases with the increase of the reaction time, and the mechanical properties show a trend of first increasing and then decreasing. Especially in Comparative Example 7, although a low-viscosity polyamic acid can be obtained, its mechanical properties deteriorate sharply and cannot maintain the expected level.

[0118] Table 3 Viscosity of polyamic acid and mechanical properties of its films at different reaction times

[0119]

[0120]

[0121] Example 12

[0122] (1) 20.024 g (0.1 mol) of 4,4′-diaminodiphenyl ether (ODA), 16.112 g (0.05 mol) of 3,3′,4,4′-diphenyl ether tetracarboxylic acid dianhydride (BTDA) and 10.470 g (0.048 mol) of pyromellitic acid dianhydride (PMDA), 98 g of DMAc and 11 g of NMP solvent were added into a container, the container was sealed and placed into a high-speed mixer, the speed was set to 2000 rpm, and the reaction was continued for 30 min. After that, 0.392 g (0.004 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 15 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 12560 mPa·s.

[0123] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0124] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 4.

[0125] Embodiment 13

[0126] (1) 10.012 g (0.05 mol) of 4,4′-diaminodiphenyl ether (ODA), 11.363 g (0.05 mol) of 4,4-diamino-benzanilide (DABA), 21.376 g (0.098 mol) of pyromellitic anhydride (PMDA), 90 g of DMAc and 10 g of NMP solvent were added to a container, the container was sealed and placed in a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 30 min, 0.392 g (0.004 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 15 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 13130 ​​mPa·s.

[0127] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0128] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 4.

[0129] Embodiment 14

[0130] (1) 10.012 g (0.05 mol) of 4,4′-diaminodiphenyl ether (ODA), 5.407 g (0.05 mol) of 1,4-phenylenediamine (PDA), 14.711 g (0.05 mol) of 3,3′,4,4′-biphenyltetracarboxylic dianhydride (BPDA) and 10.470 g (0.048 mol) of pyromellitic dianhydride (PMDA), 86 g of DMAc and 9 g of NMP solvent were added into a container, the container was sealed and placed into a high-speed mixer, the speed was set to 2000 rpm, and after the reaction was continued for 30 min, 0.392 g (0.004 mol) of maleic anhydride (MA) was added and continued to mix at 2000 rpm for 15 min to obtain a light yellow homogeneous transparent polyamic acid solution with a solid content of 30 wt% and a viscosity of 11320 mPa·s.

[0131] (2) In a clean room, the prepared polyamic acid solution is de-bubbled and then evenly coated on the surface of a clean glass plate using an automatic coating machine; then placed in a high-temperature precision thermostat for thermal imidization, and the heating program is as follows: heating from room temperature to 100°C and then keeping the temperature constant for 1 hour, heating from 100°C to 200°C and then keeping the temperature constant for 1 hour, heating from 200°C to 300°C and then keeping the temperature constant for 1 hour, heating from 300°C to 350°C and then keeping the temperature constant for 0.5 hour, and then cooling to room temperature to obtain a polyimide film.

[0132] (3) The obtained polyimide was characterized by FT-IR. Figure 1 As shown; and the mechanical properties of the polyimide film were obtained by testing according to standard GB / T 1040.3-2006, and the detailed data are listed in Table 4.

[0133] Table 4 lists the viscosity and mechanical properties of polyamic acid synthesized by copolymerization with other monomers, proving that the synthesis method is also applicable to other structures, has certain versatility, and can obtain some polyimide films with outstanding mechanical properties. For example, in Example 14, the tensile strength reaches more than 180 MPa, and the elongation at break reaches more than 80%.

[0134] Table 4 Viscosity of polyamic acid synthesized from other monomers and mechanical properties of its films

[0135]

[0136] Figure 1 It is explained that although the above embodiments and comparative examples include the same groups, the properties of the polyamic acid and polyimide film finally obtained are different through different synthesis methods and synthesis processes.

[0137] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for synthesizing a polyimide resin, characterized in that: The following steps are involved: The diamine monomer, the dianhydride monomer and the solvent are mixed and placed in a dual asymmetric centrifuge bladeless mixer, and dispersed at a rotation speed of 1000-2500rpm for 10-40min; then an anhydride compound is added and dispersed at a rotation speed of 1000-2500rpm for 5-20min to obtain a polyimide resin; the total weight of the dianhydride monomer and the diamine monomer accounts for 25wt%-35wt% of the total reaction system.

2. The synthesis method according to claim 1, characterized in that The dual asymmetric centrifuge bladeless mixer is a SpeedMixer high-speed mixer.

3. The synthesis method according to claim 1, characterized in that The viscosity of the polyimide resin is 3000-20000 mPa·s.

4. The synthesis method according to claim 1, characterized in that The diamine monomer is one or more of 4,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, benzyl diamine, diaminodiphenylmethane, ethylenediamine, propylenediamine, perfluorodiamine, and helical bisfluorenediamine.

5. The synthesis method according to claim 1, characterized in that The dianhydride monomer is one or more of pyromellitic dianhydride, 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, monoether tetracarboxylic dianhydride, hexafluoro dianhydride, benzophenone tetracarboxylic dianhydride, tetramethylbiphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, pyridine dianhydride, cyclobutane tetracarboxylic dianhydride, butane tetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride, fluorine-containing dianhydride, and silicon-containing dianhydride.

6. The synthesis method according to claim 1, characterized in that The acid anhydride compound may be one or more of maleic anhydride, norbornene dicarboxylic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride.

7. The synthesis method according to claim 1, characterized in that The solvent is a highly polar aprotic solvent.

8. The synthesis method according to claim 7, characterized in that The solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, hexamethylphosphoric triamide, acetone, pyridine and quinoline.

9. The synthesis method according to claim 1, characterized in that The molar ratio of the diamine monomer to the dianhydride monomer is 1.0:(0.95-0.995).

10. The synthesis method according to any one of claims 1 to 9, characterized in that: The molar ratio of the acid anhydride compound to the diamine monomer is 0.01-0.1:1.0.

Citation Information

Patent Citations

  • Precursor of polyimide and uses thereof

    CN101117384B

  • Low apparent viscosity polyamic acid solution and its preparation method

    CN103788651B

  • A kind of preparation method of polyimide material with high solid content and low viscosity

    CN104292459B

  • A method for synthesizing polyimide

    CN110229333B

  • Method for preparing polyamide acid composition with low viscosity and controllable solid content

    CN111808285A